Quo Vadis MPR RI: Antara Eksistensi dan Legalitas Produk? - Muchid Albintani (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2015)
The existence of the institution as People's Consultative Assembly [MPR] in the Indonesian legal and political system reform era has lost its real existence. This is due to the Assembly in the era Old Order and New Order is a tool for the rule to justify the truth in defense of the regime. While in the reforms era that have transformed the politics of law [the law of political reform], the Assembly as a whole are voters product democratic institutions 'half aspirational', representative democracy areas that can not directly create and produce regulations [legislation]. Based on the background mentioned, this paper aims to [i] Explaining the position of the Assembly as an institution of the state in the Indonesian legal and political system; [ii] Explains MPR decrees in the hierarchy [structure] of the Indonesian Legal Politics. Based on the rationale of this paper conclude two things. First, as an institution 'half aspirational', MPR has a function and authority as 'judge consent of the governed' in determining [the good, bad and fail or succeed] the implementation of the rule of law in the future. Second, because being 'judge consent of the governed', then the laws the MPR in the hierarchy of law if the Constitution as Constitutional-philosophical, the Decision [TAP] MPR can be Constitutional-Legal-Sociological Considering as a basis for policy making [ragulation] related matters a special thing for the benefit of the people.